STUDY OF INDUCED STRESS CHANGES EFFECT DUE TO CAVING ON TUNNEL DEFORMATION IN DMLZ UNDERGROUND MINE - Guhyawijaya Sri Mahabrata, Rian
Block caving is an underground mining method that utilizes the process of rock mass caving in ore extraction activities. This method can redistribute and concentrate the rock stresses in the surrounding rock of underground opening. The Deep Mill Level Zone (DMLZ) which applies the block caving method is composed of hard rock and located at a depth of ±1,700 m from the surface so the tunnel in this area has the potential to fail in brittle /spalling. The fractures that are formed can cause the volume expansion (bulking) of the rock mass where this phenomenon can be indicated by the presence of deformation around the excavation boundaries. This study aims to examine the effect of induced stress changing due to caving progress on the tunnel deformation in the DMLZ underground mine based on observations in Drill Drift 25W located in a skarn lithology. This deformation is represented by the relative displacement at the excavation boundary which can be observed using a convergence meter. Based on the bulking concept of the spalling rock mass, displacement is a function of the depth of failure (Df). The relationship between the depth of failure and the ratio of maximum in-situ stress to UCS can be determined through some analysis like empirical, observational, numerical, and some modification to fit the actual conditions (adjustment). The results of this study indicate that the displacement will increase as the cave is getting closer to the tunnel, this is correlated with the increasing stress around the opening. From the depth of failure analysis, the failure zone around the opening can be modeled numerically using Cohesion Weakening and Frictional Strengthening (CWFS) rock behavior where the rock mass will begin to spalling when the maximum stress is ±45% of UCS and will expand by ±5% of Df. In order to anticipate the displacement that exceeds the ground support capacity threshold, support maintenance is required to maintain the tunnel stability and factor of safety.